Diversity of aphids and their natural enemies in forest areas of northwestern Algeria, with a new record of Myzocallis schreiberi - Amine Akrich; Kada Righi; Fatiha Assia Righi; Abdelwahab Chedad; George Japoshivli (Journal of Basic and Applied Zoology)
Abstract Background Aphids are piercing-sucking insects that can cause many problems for plants in different environments, such as the trees and shrubs of forest ecosystems. However, aphids are an important part of the food chain. Aphids provide food for numerous predators and serve as a source of reproduction for numerous parasitoid species. This aids in maintaining the equilibrium of the environment. Results We conducted the current study, based on weekly visual sampling of aphids and their natural enemies, in two forests with a total area of 31 hectares located in northwestern Algeria from February to June 2021 and 2022. We recorded twenty aphid species on fourteen tree and shrub species, including the Holm oak aphid, Myzocallis schreiberi, which is a first for Algeria. This study has also revealed 12 species of predators belonging to five families, as well as four species of primary parasitoids belonging to the Braconidae family. The most abundant predator in the aphid population was the species Coccinella algerica (Linnaeus, 1758), while Lysiphlebus fabarum (Marshall, 1896) was the most abundant parasitoid. Conclusions Natural enemies, such as predators and parasites, play a crucial role in controlling populations of aphids. By protecting the survival and reproduction of natural enemies, we can help maintain a diverse and healthy ecosystem.